The day after tomorrow : a handbook on the future of economic policy in the developing world - Canuto, Otaviano; Giugale, Marcelo (Washington, D.C. : World Bank, 2010)
The book shows the views of some development economists, most of them from the world bank poverty reduction and economic management network, on what the developing world would become in the future.
Includes bibliographical references and index.
nif 25/04/13
Loans
Keywords: Poverty; Economic policy; Developing world; Developing countries